USING WORD ANALOGIES TO IMPROVE THE ENGLISH VOCABULARY MASTERY OF THE STUDENTS AT SMP NURUL QALAM (Karya Ilmiah Mahasiswa (KIMA), 2023)
Vocabulary is the all the language and words either used or understood by a person or group of people. And a word analogy is a comparison of two otherwise unlike things based on resemblance of a particular aspect, inference that it two or more things agree with one another in some respects they will probably agree in others. This research aimed to know whether or not the use of word analogy to improve the students vocabulary mastery. This research employed pre experimental method. The population of the research was the second grade students of SMP Nurul Qalam in academic year 2021-2022. The total sample of this research was 30 students from VIII.A class. The technique of sampling was cluster random technique. The data were obtained through vocabulary test. The vocabulary test aims to find out the students' vocabulary mastery by using word analogy. The result of data analysis showed that there were the differences between the students' score in pre-test and in post-test. It is proved by the mean score of the students post-test that it higher than pre-test. The mean score in pre-test was 37.28 and in post-test was 71.03. Moreover, the result of the test indicates that using Word Analogy improve the students' vocabulary mastery. Based on the result of analysis, the researcher concluded that using word analogy improves the students' vocabulary mastery of the second grade students of SMP Nurul Qalam in academic year 2021/2022.